(untitled) (Research, Society and Development, 2022)
This topic is approached through a case study of a textile industry located in São Paulo. The textile melioration process was selected to have its capacity analyzed. The choice of these stages of the production chain is based on the fact that they are the main production processes within the company that involve a large flow of raw materials and labor. The results of this research serve to review and analyze the total manufacturing costs of items produced in the company. And also for future economic studies of the production chain, creating an academic reference on the subject.